2017
DOI: 10.1021/acs.jmedchem.7b00533
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of R/S-N-3-Cyanophenyl-N′-(6-tert-butoxycarbonylamino-3,4-dihydro-2,2-dimethyl-2H-1-benzopyran-4-yl)urea, a New Histone Deacetylase Class III Inhibitor Exerting Antiproliferative Activity against Cancer Cell Lines

Abstract: A new series of N-aryl-N′-3,4-dihydro-2,2-dimethyl-2H-1-benzopyran-4-yl)ureas bearing an alkoxycarbonylamino group at the 6-position were synthesized and examined as putative anticancer agents targeting sirtuins in glioma cells. On the basis of computational docking combined to in vitro sirtuin 1/2 inhibition assays, we selected compound 18 [R/S-N-3-cyanophenyl-N′-(6-tert-butoxycarbonylamino-3,4-dihydro-2,2-dimethyl-2H-1-benzopyran-4-yl)urea] which displays a potent antiproliferative activity on various glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Docking studies were carried out as previously reported [54] using the Protein Data Bank (PDB) codes 4BKX, 4LY1, 4A69, 2VQM, 5EDU, 3C10, and 3EW8 corresponding to HDAC1, HDAC2, HDAC3, HDAC4, HDAC6, HDAC7, and HDAC8, respectively. MAKV-6, MAKV-7, MAKV-8, MAKV-10, and MAKV-12, and SAHA were drawn using ChemDraw Professional software version 15.0 (PerkinElmer Informatics).…”
Section: Docking Studiesmentioning
confidence: 99%
“…Docking studies were carried out as previously reported [54] using the Protein Data Bank (PDB) codes 4BKX, 4LY1, 4A69, 2VQM, 5EDU, 3C10, and 3EW8 corresponding to HDAC1, HDAC2, HDAC3, HDAC4, HDAC6, HDAC7, and HDAC8, respectively. MAKV-6, MAKV-7, MAKV-8, MAKV-10, and MAKV-12, and SAHA were drawn using ChemDraw Professional software version 15.0 (PerkinElmer Informatics).…”
Section: Docking Studiesmentioning
confidence: 99%
“…The natural SIRT inhibitor nicotinamide was also included as a reference compound for in vitro SIRT3 inhibition [ 34 ]. Besides suramin, additional references SIRT1/2, SIRT1, and SIRT2 inhibitors, namely, sirtinol, EX-527, and AGK2, respectively, performed in a similar range or less efficiently [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Docking studies were performed as previously described [ 15 ] with a docking grid size of 25 Å × 25 Å × 25 Å, which encompassed the entire inhibitor binding pocket of SIRT1 and 2 structures. To prepare the SIRT coordinates for docking simulation, ligands and all water molecules were removed except static water molecules in the binding site that could play important roles in the actual inhibition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations